Determination of spatial interaction of the individual road train links - Orisenko, O; Skoryk, M.; Kryvorot, A; Rassoha, I. (Academic journal Industrial Machine Building Civil Engineering, 2022)
When designing traction-coupling devices and studying the operational properties of road trains, it becomes necessary to determine the size and direction of applying loads that are transmitted from one link of the road train to another. This is convenient to carry out, first by designing a spatial system of forces acting on a separate link, on the axis of the spatial coordinate system, which is fixedly connected with this link, and then bringing these projections to the coordinate system, which is fixedly connected with another link. So, the problem is to develop a mathematical apparatus that allows you to make the transition between coordinate systems that are rigidly connected with individual links of the road train. For a category M1 road train, it is proposed to make a transition between coordinate systems using a table, which is a transformed product of rotation matrices around the coordinate system axes, which is accepted as stationary. At the same time, stationary, depending on the task, can be considered a coordinate system associated with any link of the road train. Since the product of matrices is not commutative, and the positions of individual links during movement change all the time according to an arbitrary sequence of turns, the resulting matrix will depend on the accepted sequence of turns, which will further affect the projections magnitude of the force one link influences on another part.
Keywords: road train; rotation angles; rotation matrix; stationary and moving coordinate systems; traction-coupling device; tractor car; trailer